The Effectiveness Of The School Principal's Managerial Supervision On The Quality Of School Education At The Junior High School Level - Maisura Maisura; Bahrun Bahrun; Nasir Usman; Jafalizan Md. Jali (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to determine the effectiveness of principal supervision on the quality of school education in SMP Negeri 1 Sigli and SMP YPPU Sigli. This study uses a quantitative method using 2 variables, namely the principal's managerial supervision variable (X), and the quality of education (Y). The participants consisted of 4 people, including 1 Principal of SMP Negeri 1 Sigli and SMP YPPU Sigli, as well as 2 supervisors, and the Head of Curriculum as a teacher selected by purposive sampling technique. Data collection techniques used consist of two kinds, namely interview techniques, and questionnaire techniques. Data analysis techniques use prerequisite tests and hypothesis tests. The results showed that the correlation coefficient (R) of 0.644 showed a high relationship between principals' managerial supervision and education quality. The principal's managerial supervision variable affects the education quality variable by 41.4%. The implication of this research shows that principals' management supervision is effective in improving the quality of school education.